Brazilian New Foreign Policy and Implications within BRICS - Ana Luiza Bravo e Paiva; Cintiene Sandes Monfredo Mendes; Victor Carneiro Corrêa Vieira (Journal of China and International Relations, 2020)
On the dawn of the 2008 financial crisis, Brazil, Russia, India, and China celebrated the first BRIC's Summit, in 2009, till the bloc foundation in 2006. At that time, the four countries were responsible for 65 percent of the world’s total economic growth and was aimed at the reform of the international institutions so that they would reflect the emerging countries' economic rise in international politics. The group was directly related to each of the members' goals of development‚ which was a historical purpose of Brazilian foreign policy articulated at that time in Celso Amorim's "Active and Generous Foreign Policy." Nevertheless, the election of Jair Bolsonaro for the Brazilian presidency in 2018 brought a revision of the country's foreign policy. Since Ernesto Araujo took office as Brazil's current Minister of Foreign, in January 2019, he proposed a rebrand under the name of "New Foreign Policy," reformulating basic principles as a return to the concepts of Americanism over the previous Multilateralism, a denouncement of "Globalism," and a strong defense of Christianity. This article will provide a discourse analysis of the first year of this mandate to observe how Brazil's "New Foreign Policy" could affect the BRICS bloc. The preliminary evidence points to the retraction of the BRICS agenda in Brazilian external actions due to the new Brazilian political approach.